Ageing and Care for Frail Elderly Persons An Overview of International Perspectives - Jacobzone, Stephane (OECD Publishing, 1999)
This paper examines the various constraints which OECD Member countries must now deal with, faced with the prospects of rapid growth in the number of frail elderly persons. It pays particular attention to recent trends in disability. Most of the available cross-country evidence shows trends towards better functional health in older populations, although the magnitude of the gains and their significance need further assessment. In this context, this paper advocates an "active ageing" approach to long-term care policies. It provides some rough estimates of the macroeconomic costs of long-term care. It also presents some indicators of public/private financing and institutionalisation rates. The public costs of providing long-term care are estimated to be relatively modest as a proportion of GDP (of the order of 1 or 2 per cent or less). However, much care for the frail elderly is provided through informal care-giving arrangements which are not reflected in official figures
Keywords: Social Issues/Migration/Health